Padrões privados no Direito da OMC: estudo a partir da codificação e prática da responsabilidade internacional do Estado por atos de particulares - Arneiro, Alexandre Cardeal de Oliveira (2017)
This dissertation aims to analyse the responsibility of WTO Member for the so-called private standards, in the light of the State responsibility in international law for the acts of private persons. It proposes a dialogue of integration of the general international law, understood as lex generalis, with the WTO law, that is the lex generalis assuming the hypothesis that the application of States international practice supposedly gives more unity to international public law and effectiveness to WTO law. The development of the research is justified in the exploratory and hypothetic-deductive method, from the functions of the State international responsibility and the conventional and consuetudinary rules codified by the International Law Comission (ILC). The Agreements TBT and SPS foresee the Members’ duty to assure that the agreement provisions, v.g. the most favoured nation principles and the prohibition of unnecessary or excessive non-tariff barriers, should be accomplished also by the nongovernmental standardizing bodies. With that regard this study approaches the categories of State responsibility for private acts stated on the ILC Draft Articles of 2001 to the situations where Members can incur in responsibility for involvement. This assertion is valid not only for the TBT Agreement but also to SPS Agreement, thanks to the interpretative function of the lex generalis. Finally it confirms the hypothesis that application of international responsibility law, as a soft law, ought contribute to effectiveness of WTO law, as it impedes Members to use ways of damaging thirds, though mechanisms of collaboration with private parties under their control, supervision or direction